Gypsum treatment in managing the internal phosphorus load from sapropelic sediments; experiments on Lake Laikkalammi, Finland - Salonen, V.-P.; Varjo, E.; Rantala, P. (Boreal Environment Research Publishing Board, 2024)
The sediment of the hypertrophic Lake Laikkalammi, (area 8000 m2, max. depth 13 m) in southern Finland was treated with the industrial by-product Fe-gypsum (CaSO4 x 2H2O) in summer 1998. A 90% reduction of the hypolimnic total phosphorus content was achieved and Secchi disk transparency increased from 50 cm to 270 cm during one year long observation period. Gypsum is hypothesized to limit the internal load through three interacting mechanisms: as a mechanical cover limiting the resuspension and gas ebullition, as a chemical offering binding sites for phosphorus (Ca, Fe) and finally by changing the microbiological composition of sediment by creating more favorable conditions for sulphur bacteria instead of methane bacteria. Fe-gypsum treatment can be seen as a complementary lake restoration method that is suitable for relatively deep, small lakes in which the water quality problems are a consequence of internal loading caused by oxygen deficiency in the hypolimnion.